Papillary thyroid microcarcinoma with contralateral large humerus metastasis and cervical lymph node metastasis: A case report - Gong, Yi; Tang, Shixiong; Tan, Wanlin; Liao, Liyan; Li, Xiaodu; Niu, Chengcheng (Frontiers in Oncology, 2022)
Introduction Papillary thyroid microcarcinoma (PTMC) that metastasizes to bone, especially metastasizes to contralateral humerus with so large mass, is rarely reported before. Case report We presented a 50-year-old female patient with a large painful mass in the right humerus for 5 years, presenting with swelling of the right shoulder with limited mobility. Positron emission tomography–computed tomography (PET/CT) showed a large mass in the right humerus, bilateral lung lesions, and enlarged lymph nodes in the right supraclavicular fossa. Right humerus lesion biopsy and immunohistochemical evaluations confirmed that the lesion originated from the thyroid tissue. Then, the thyroid ultrasonography showed a hypo-echoic solid nodule with an irregular taller-than-wide shape in the upper of left thyroid lobe and enlarged lymph nodes with the absence of fatty hilum in the contralateral right IV compartment. The total thyroidectomy and cervical lymph node dissection were undertaken; the histopathology confirmed the diagnosis of PTMC with contralateral cervical lymph node metastasis. Conclusion We reported a case of PTMC with contralateral large humerus and cervical lymph node metastasis and demonstrated the PET/CT images of the metastatic large humerus and thyroid ultrasonographic appearances of the PTMC and enlarged cervical lymph node.